Cholesterol Chip for the Study of Cholesterol–Protein Interactions Using SPR - Peng He; Shannon Faris; Reddy Sudheer Sagabala; Payel Datta; Zihan Xu; Brian Callahan; Chunyu Wang; Benoit Boivin; Fuming Zhang; Robert J. Linhardt (Biosensors, 2022)
Cholesterol, an important lipid in animal membranes, binds to hydrophobic pockets within many soluble proteins, transport proteins and membrane bound proteins. The study of cholesterol–protein interactions in aqueous solutions is complicated by cholesterol’s low solubility and often requires organic co-solvents or surfactant additives. We report the synthesis of a biotinylated cholesterol and immobilization of this derivative on a streptavidin chip. Surface plasmon resonance (SPR) was then used to measure the kinetics of cholesterol interaction with cholesterol-binding proteins, hedgehog protein and tyrosine phosphatase 1B.